Societies and military power : India and its armies - Rosen, Stephen Peter, 1952- (Cornell studies in security affairs., 1996)
A work with broad implications for theories of comparative strategic behavior and civil-military relations, Societies and Military Power uses the long history of the armies of India as a basis for analyzing whether the amount of military power that can be generated by the armies that emerge from that society. By examining the changing relationship between ruling elites in the Indian subcontinent and their armed forces, the book shows that divisions within society are mirrored within the military, even within the contemporary professional military. Stephen Peter Rosen explores the proposition that cultural explanations don't sufficiently account for changes in military power, whereas social structure does. He suggests also that the dynamics of civil-military relations in a non-Western setting are not explicable without social-structural insight. He concludes that the comparative study of strategic behavior and military organization has lacked a sound foundation, which the social-structural explanation offered in this book begins to provide.